POLITICAL DYNAMICS BEHIND THE MAKING OF SHARĪ‘AH-INSPIRED BYLAWS IN SURAKARTA: The Case of Bylaw Number 3/2006 on the Eradication of Prostitution (JOURNAL OF INDONESIAN ISLAM, 2021)
This article discusses how Islamic law was made (al-tashrī’ al-Islamī) to fit into Bylaw Number 3, 2006 about the Eradication of Commercial Sexual Exploitation in the City of Surakarta, Central Java. The creation of this bylaw saw heated debates about the ideological understanding of religious life of the purists and political discord among different fractions in the Regional House of People’s Representatives (Dewan Perwakilan Rakyat Daerah, DPRD) of the City of Surakarta. Even though much debate went on, agreement was finally reached that the widespread prostitution and commercial sexual exploitation in the city had to be stopped because it caused moral damages on children and teenagers. This agreement was reached to meet the objective of al-tashrī’ (maqāṣid al-sharī‘ah) or in order to create a condition of harmony in accordance with moral values and religious norms. To present a complete picture, this study uses the grounded research on how law was made on the basis of different interests either at political or ideological level.